Problematics of the Village Government Authority - Ahmad Yamin; Supriyadi Supriyadi (Unram Law Review, 2020)
The purpose of this research is to analyze the authority problems of the village government. This is a doctrinal legal research by examining legal materials from libraries or research libraries to obtain secondary legal material from books, articles, research results, and regulations, as well as experts relating to the exercise of villages authority. The solution offered is that the authority of the village government will run well when it is support by the authority of recognition and subsidiarity and the availability of human resources who have expertise and skills and apply good governance to create a village social welfare.